The Impact of an Occluded Internal Carotid Artery on the mortality and morbidity of patients undergoing Coronary Artery Bypass Grafting - M Abbaszade Ghanavati; A Rabbani; SH Ahmadi; E Jazayeri (Tehran University of Medical Sciences, 2008)
Background and Aim: Stroke is an important cause of morbidity and mortality in patients undergoing coronary artery bypass (CABG) surgery. There are various mechanisms that can cause prioperative strokes in patients undergoing CABG other than Carotid Artery disease. The goal of this study is to evaluate whether the presence of stenosis internal carotid artery (ICA) influences prioperative stroke and mortality rates in patients subjected to Coronary Artery Bypass Grafting.  Materials and Methods: After institutional ethical committee review and approval, a retrospective review was undertaken of 1978 bypass procedures with saphenous vein graft performed over a period of four years is conducted. All those who had valve replacement or non-CABG procedure were excluded from this study. Carotid duplex ultrasonography scans were performed as part of preoperative evaluation of these patients. Ultrasound imaging measurement and velocity criteria were taken in to consideration in the estimation of degree of the carotid arteries. The stenosis of ICA was classified as non significant stenosis when there was<60% narrowing of the arterial lumen, and significant stenosis when there was 60%-99% narrowing of the arterial lumen. Results: prioperative stroke rates were 0.8 %, 46.8% and 90%for groups A, B, and C, respectively. Group A results varied significantly from group's B (P=0.0001) and C (P=0.0001). Statistically significant difference was noted between groups B and C (p=0.0001    ). Prioperative mortality rates for groups A, B, and C, were 1.0 %, 16.7 % and 70 % respectively. The mortality rate for group A was lower than for groups B (P=0.0001) and C (P=0.0001). Conclusion: The presence of an ICA occlusion increases the morbidity and mortality in patients undergoing CABG.